Antidiarrhoeal activity of Sri Lankan Dust grade Black Tea (Camellia sinensis L.) in mice - Ratnasooriya, W.D.; Fernando, T.S.P. (My University, 2009)
This study examined the antidiarrhoeal potential of Sri Lankan black tea (Camellia sinensis) in mice using high grown unblend Dust grade No; 1 tea. Different concentrations of black tea brew (BTB) [84 mg/ ml (equivalent to 1.5), 167 mg/ ml (equivalent to 3), 501 mg/ ml (equivalent to 9) or 1336 mg/ ml (equivalent to 24)], or a high concentration (equivalent to 9 cups) of green tea brew (GTB) of Chinese and Japanese types or reference drug, loperamide (10 mg/ kg) were orally administered to different groups of mice {N = 9-12/group) and were subjected to two antidiarrhoeal tests: normal defecation test and castor oil-induced diarrhoea test. The results show that BTB of Sri Lankan Dust grade tea dose-dependently and markedly decreased the number of faecal boluses produced in the normal defecation test and improved the severity of the diarroheal condition in the castor oilinduced diarrhoea test. However, the antidiarrhoeal effect of BTB was superior to Japanese type of GTB and inferior to loperamide. BTB also prolonged the gastrointestinal transit time, impaired intestinal fluid secretion, increased intestinal fluid absorption and reduced in vitro nitric oxide production. It is concluded that Sri Lankan black tea possesses marked antidiarrhoeal activity which is mediated via multiple mechanisms. The finding also supports the folkloric claim that Sri Lankan black tea is a good remedy for acute non specific diarrhoea.